Aboriginal Family Services Agencies in High Poverty Urban Neighborhoods: Challenges Experienced by Local Staff - Brown, Jason; Fraehlich, Cheryl (First Peoples Child & Family Review, 2011)
The purpose of the study was to describe the challenges of working in the community from the perspective of staff hired locally by culturally-based Aboriginal organizations in high-poverty urban neighborhoods. Locally staffed and culturally based Aboriginal family service agencies operating communities with high levels of poverty have emerged in large cities. Efforts of these agencies are consistent with community economic development practice aiming to improve local quality of life and skill development and promote economic capacity. There has been little research to date exploring the challenges faced by staff working in these organizations. Participants were residents of the local geographic community and staff of one of three Aboriginal family services agencies in a large Canadian city. They were asked “What are the challenges of working in your own community?” and their responses were analyzed using concept mapping methodology. Twelve concepts emerged from the analysis including: lack of privacy, being personally affected outside of work, keeping healthy boundaries, and knowing how to help. In addition participants described the high local need and meeting the range of needs given limited funding and influence of government on operations. As well, participants identified dealing with broader structural issues, such as substance abuse and gang problems. The results indicate that staff in Aboriginal family services agencies in high poverty communities experience living in the same community as service recipients, management of personal relationships with them, diversity of need within their service area, as well as potential for traumatic experiences as particularly challenging. Staff preparation, training and support for these issues are important for funders and administrators to attend to.